2022
DOI: 10.2147/ppa.s340621
|View full text |Cite
|
Sign up to set email alerts
|

Polypharmacy, Medication-Related Burden and Antiretroviral Therapy Adherence in People Living with HIV Aged 50 and Above: A Cross-Sectional Study in Hunan, China

Abstract: Purpose People living with HIV (PLWHIV) are susceptible to non-communicable diseases (NCDs) because of aging and infections. This means that the number of non-HIV medications increases, along with issues of polypharmacy and medication-related burden. The purpose of this study was to identify the current situation of polypharmacy and medication-related burden among PLWHIV aged 50 and above, as well as the relation between medication-related burden and antiretroviral therapy (ART) adherence. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…58% of participants knew of the medication file, however, only 40% of pharmacists reported to offering it systematically. 32% of participants would like to use the medication file programme, particularly those with shorter ARV duration, a less often undetectable viral load and those who experience anxiety more often Generalisability of the study results are reduced due to the sample population being predominantly male Zheng et al, 2022 (China) [ 61 ] n = 185 M = 58 years (SD = 7.5) Hospital and community Data were collected using questionnaires The Chinese version of the Living with Medicines Questionnaire version 3 (LMQ-3) and the Centre for Adherence Support Evaluation (CASE) Adherence Index Polypharmacy was reported in 40% of participants. A higher level of medicine-related burden was reported in females, who took more drugs and had a lower monthly income.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…58% of participants knew of the medication file, however, only 40% of pharmacists reported to offering it systematically. 32% of participants would like to use the medication file programme, particularly those with shorter ARV duration, a less often undetectable viral load and those who experience anxiety more often Generalisability of the study results are reduced due to the sample population being predominantly male Zheng et al, 2022 (China) [ 61 ] n = 185 M = 58 years (SD = 7.5) Hospital and community Data were collected using questionnaires The Chinese version of the Living with Medicines Questionnaire version 3 (LMQ-3) and the Centre for Adherence Support Evaluation (CASE) Adherence Index Polypharmacy was reported in 40% of participants. A higher level of medicine-related burden was reported in females, who took more drugs and had a lower monthly income.…”
Section: Resultsmentioning
confidence: 99%
“…Older PLWH are more likely to be affected by anxiety, depression, cancer, chronic kidney disease (CKD), chronic pain, diabetes, hypertension, osteoporosis, hepatitis B/C infections than HIV-negative individuals [ 31 , 32 , 34 , 36 , 39 , 42 – 45 , 47 , 51 , 55 , 58 , 61 ]. A study comparing HIV-positive older males to their HIV-negative counterparts found that older participants were six times more likely to be diagnosed with osteoporosis [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding has been observed also in elderly subjects without HIV infection 28 . Otherwise, comorbidities and polypharmacy, could have contributed to a worse immune as well as virologic outcome in older PLWH 29 .…”
Section: Discussionmentioning
confidence: 99%